Influence of oxidative stress on the activity of mTOR kinase in CD4+T lymphocytes in autoimmune thyroiditis - A. V. Burtseva; A. N. Tikhonova; Z. A. Afanasyeva; Z. I. Abramova (Медицинская иммунология, 2025)
Currentstudies of autoimmunityprocesses areaddressing specific processes involving mitochondria, i.e., altered intracellular signaling including the generation of ROS and release of proteins from mitochondria to the cytoplasm, thus activating apoptosis. These functions of mitochondria are usually associated with disturbed bioenergetic functions and excessive production of H2O2. Currently, a new area is actively developing, i.e., potential participation of mitochondria in the immune response. Therefore, the aim of the present study was to evaluate the dynamics of apoptosis factors and autophagy associated with mitochondria of CD4+T cells in autoimmune thyroiditis (AIT). The study was performed with CD4+T cells of AIT patients and healthy donors obtained by magnetic separation. Apoptosis and autophagy were assessed by flow cytometry. Western blotting was used to analyze autophagy marker proteins (p62, LC3I/II, mTOR kinase), and apo ptosis regulator Bcl-2 in CD4+T lymphocytes of the patients and donors. The state of mitochondria in CD4+T lymphocytes was assessed by confocal microscopy. Using an experimental model with increased H2O2, we showed that ROS activate LC3 protein in cells of patients with AIT along with accumulation of autophagic adapter protein p62, as registered on the outer mitochondrial membrane. An increased level of mitophagoses was found in CD4+T cells from the AIT patients. On the basis of these data, one may assume that H2O2 causes activation of mitophagy in CD4+T cells of patients with AIT, and the development of oxidative stress with excessive production of ROS leads to irreversible damage to mitochondria, which causes a decreased apoptotic activity followed by development of secondary necrosis of CD4+T lymphocytes in AIT, making them cytotoxic. Accumulation of such cells in the thyroid tissue may lead to impaired apoptosis in thyrocytes and, as a consequence, to secondary necrosis, thus resulting in development of autoimmune response. The obtained data require additional studies, since the detection of CD4+T lymphocytes prone for apoptosis or necrosis in patients with AIT may be used as a diagnostic criterion for prediction of inflammatory conditions.